[RuIII(EDTA)(H2O)]− mediated oxidation of cellular thiols by HSO5−. (3rd October 2016) - Sarkar, Papiya; Saha, Amrita; Chatterjee, Debabrata
Abstract : [Ru III (EDTA)(H2 O)] − (EDTA 4− = ethylenediaminetetraacetate) effectively catalyzes the oxidation of thiols (RSH) to produce disulfides (RSSR) using KHSO5 as an oxidant. Abstract : The [Ru III (EDTA)(H2 O)] − (EDTA 4− = ethylenediaminetetraacetate) complex is shown to mediate the oxidation of thiols, RSH (RSH = cysteine, glutathione, N -acetylcysteine, and penicillamine), with peroxomonosulfate ion (HSO5 − ). The kinetics of the catalytic oxidation process were studied using stopped-flow and rapid scan spectrophotometry as a function of [Ru III (EDTA)(H2 O) − ], [HSO5 − ], and [RSH] at a constant pH (6.2). Spectral analyses and kinetic data are suggestive of a catalytic pathway in which the RSH reacts with the [Ru III (EDTA)] catalyst complex to form [Ru III (EDTA)(SR)] 2− intermediate species. In a subsequent step the HSO5 − ion reacts directly with the coordinated S-atom of [Ru III (EDTA)(SR)] 2− yielding the disulfido species, RSSR, as a major oxidation product (as identified using HPLC and ESI-MS analyses) under the employed conditions. Based on the experimental data, a working mechanism is proposed for the [Ru III (EDTA)] catalyzed oxidation of thiols.